2020
DOI: 10.3390/microorganisms8071014
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation by a Combination of Different Peak-Wavelength Ultraviolet-Light Emitting Diodes Enhances the Inactivation of Influenza A Viruses

Abstract: Influenza A viruses (IAVs) pose a serious global threat to humans and their livestock. This study aimed to determine the ideal irradiation by ultraviolet-light emitting diodes (UV-LEDs) for IAV disinfection. We irradiated the IAV H1N1 subtype with 4.8 mJ/cm2 UV using eight UV-LEDs [peak wavelengths (WL) = 365, 310, 300, 290, 280, 270, and 260 nm)] or a mercury low pressure (LP)-UV lamp (Peak WL = 254 nm). Inactivation was evaluated by the infection ratio of Madin–Darby canine kidney (MDCK) cells or chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The DUV region is usually defined as the wavelength range from 200 nm to 300 nm. Photochemical inactivation of viruses and microorganisms is most effective with UV-C photons in the 100- to 280-nm wavelength range with a peak effectiveness near 265 nm, which is the approximate absorption maximum wavelength for DNA and RNA ( 2 , 3 ). UV light in the longer wavelength range, classified as UV-A (320 to 400 nm) and UV-B (280 to 320 nm), also inactivates SARS-CoV-2; however, the efficiency is relatively low compared with that of UV-C ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The DUV region is usually defined as the wavelength range from 200 nm to 300 nm. Photochemical inactivation of viruses and microorganisms is most effective with UV-C photons in the 100- to 280-nm wavelength range with a peak effectiveness near 265 nm, which is the approximate absorption maximum wavelength for DNA and RNA ( 2 , 3 ). UV light in the longer wavelength range, classified as UV-A (320 to 400 nm) and UV-B (280 to 320 nm), also inactivates SARS-CoV-2; however, the efficiency is relatively low compared with that of UV-C ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…A lGaN-based deep ultraviolet light-emitting diodes (DUV-LEDs) are expected to replace mercury lamps to reduce environmental load and power consumption and are currently under development for other applications such as sterilization, resin curing, phototherapy, and photocatalytic excitation. In particular, recently, it has been reported that UV light is promising for inactivating the COVID-19 virus, [1][2][3] and the use of LEDs has also been proposed. 1,2) For AlGaNbased DUV-LEDs, owing to the improvement of the quality of the high-Al-composition AlGaN layer and the optimization of the LED design, many research groups report external quantum efficiencies (EQEs) exceeding 5% in the emission wavelength range of 270-300 nm, and some research groups are even reporting EQEs exceeding 10%.…”
mentioning
confidence: 99%
“…In particular, recently, it has been reported that UV light is promising for inactivating the COVID-19 virus, [1][2][3] and the use of LEDs has also been proposed. 1,2) For AlGaNbased DUV-LEDs, owing to the improvement of the quality of the high-Al-composition AlGaN layer and the optimization of the LED design, many research groups report external quantum efficiencies (EQEs) exceeding 5% in the emission wavelength range of 270-300 nm, and some research groups are even reporting EQEs exceeding 10%. [4][5][6][7][8][9] However, the efficiency of DUV-LEDs is still significantly lower than that of blue LEDs (> 80%).…”
mentioning
confidence: 99%
“…Regarding viruses, Kojima et al. in 2020 also showed that 260 nm UV-LEDs were more effective to inactivate influenza A viruses than LP lamps [ 16 ]. Oguma, Rattanakul and Bolton also showed that 285 nm UV-LEDs have higher performance than LP UV lamps for adenoviruses and therefore 285 nm UV-LEDs could be a good option to inactivate adenoviruses in water [ 17 ].…”
Section: Introductionmentioning
confidence: 99%